Long-term trends of BMI and cardiometabolic risk factors among adults with type 1 diabetes: An observational study from the German/Austrian DPV registry. (August 2021) - Welters, Alena; Tittel, Sascha R.; Laubner, Katharina; Laimer, Markus; Tschöpe, Diethelm; Mader, Julia K.; Merger, Sigrun; Milek, Susanne; Kummer, Sebastian; Holl, Reinhard W.
Highlights: The prevalence of obesity increased 1.8-fold in individuals with T1DM (1999–2018) Obesity increased faster in individuals with T1DM than in the German population. The rise in BMI was most pronounced during young adulthood. Long diabetes duration and high insulin doses increase the risk for rising BMI. CV risk factors are insufficiently managed in > 50% of obese individuals with T1DM. Abstract: Aims: To analyse time-trends in BMI, obesity and cardiometabolic risk in adults with type 1 diabetes (T1DM) from the Diabetes Prospective Follow-up registry DPV. Methods: Data from 62, 519 individuals with T1DM (age ≥ 18 years, BMI ≥ 18.5 kg/m 2 ) were analysed. Multivariable regression models were used to determine time-trends in BMI, obesity and cardiometabolic risk and to identify predictors for increasing BMI. Results were compared to the NCD Risk Factor Collaboration (NCD-RisC) data for Germany. Results: Between 1999 and 2018 mean BMI increased from 25.0 kg/m 2 to 26.2 kg/m 2 in individuals with T1DM. This trend was most pronounced in young and middle-aged individuals (>21–55 years of age) and in those with higher baseline BMI. Insulin dose and diabetes duration were associated with increasing BMI. Between 1999 and 2016, the prevalence of obesity increased 1.8-fold in individuals with T1DM and 1.4-fold among the German population, respectively (NCD-RisC). Approximately 50–70% of individuals with obesity were insufficiently treated for hypertension and/or dyslipidaemia. Conclusion: In adults with T1DM the prevalence of obesity is increasing at a faster pace than in the German population. BMI needs to be closely monitored, particularly during young adulthood, and cardiovascular risk factors need to be controlled better to prevent CVD and premature death.